Comparison of extruded and sonicated vesicles for planar bilayer self-assembly - Cho, Nam-Joon (2013)
Lipid vesicles are an important class of biomaterials that have a wide range of applications, including drug delivery, cosmetic formulations and model membrane platforms on solid supports. Depending on the application, properties of a vesicle population such as size distribution, charge and permeability need to be optimized. Preparation methods such as mechanical extrusion and sonication play a key role in controlling these properties, and yet the effects of vesicle preparation method on vesicular properties and integrity (e.g., shape, size, distribution and tension) remain incompletely understood. In this study, we prepared vesicles composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) lipid by either extrusion or sonication, and investigated the effects on vesicle size distribution over time as well as the concomitant effects on the self-assembly of solid-supported planar lipid bilayers. Dynamic light scattering (DLS), quartz crystal microbalance with dissipation (QCM-D) monitoring, fluorescence recovery after photobleaching (FRAP) and atomic force microscopy (AFM) experiments were performed to characterize vesicles in solution as well as their interactions with silicon oxide substrates. Collectively, the data support that sonicated vesicles offer more robust control over the self-assembly of homogenous planar lipid bilayers, whereas extruded vesicles are vulnerable to aging and must be used soon after preparation.